2021
DOI: 10.5337/2021.223
|View full text |Cite
|
Sign up to set email alerts
|

Gender dimensions of solid and liquid waste management for reuse in agriculture in Asia and Africa

Abstract: Resource Recovery and Reuse (RRR) is at the core of the circular economy and particularly important in an urbanizing world where cities as consumption hubs become vast sinks of usually wasted resources. To recover the value which wastewater and organic (food) waste, in particular, can offer agriculture, there are many entry and scaling barriers for entrepreneurs to realize the required potential of the circular economy, and these are even higher for women. Different challenges apply to efforts increasing safe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Lystek International offers biosolids processing solutions for municipal wastewater treatment plants and organic waste materials from industrial, commercial and agricultural sectors. 21 The company offers patented design and build services to implement thermal hydrolysis and associated systems. It also produces LysteGro, a pathogen-free, nutrient-rich fertilizer that meets the standards of a USEPA Class A material.…”
Section: Lystek International Inc Usamentioning
confidence: 99%
See 1 more Smart Citation
“…Lystek International offers biosolids processing solutions for municipal wastewater treatment plants and organic waste materials from industrial, commercial and agricultural sectors. 21 The company offers patented design and build services to implement thermal hydrolysis and associated systems. It also produces LysteGro, a pathogen-free, nutrient-rich fertilizer that meets the standards of a USEPA Class A material.…”
Section: Lystek International Inc Usamentioning
confidence: 99%
“…https://www.cleanaway.com.au/waste/biosolids-waste-management/ (accessed on September 12, 2022) 20 https://www.severntrent.com/sustainability-strategy/environment/bioresources/biosolids/ (accessed on April 24, 2023)21 https://lystek.com/ (accessed on August 10, 2022)…”
mentioning
confidence: 99%
“…Women play an important informal role in the management and use of wastewater (International Labour Organization 2017), in addition to which Ungureanu, Vlăduț and Voicu (2020) identify women and children as being at particular risk of disease from eating food produced with wastewater. The development of policies and interventions needed to realize benefits from wastewater resource recovery and reuse will require a gendered perspective to ensure solutions are both safe and appropriate (Taron, Drechsel and Gebrezgabher 2021; see also case study 16 -Georgia). The WWAP Water and Gender Working Group's Call to Action for accelerating gender equity across the water domain was adopted in 2021 and included a road map to ensure successful delivery of the 2030 Agenda.…”
Section: Potential Contribution To Be Gained From Improved Wastewater...mentioning
confidence: 99%
“…Quality standards: Quality standards for the reuse and return of wastewater to the environment have been evolving since the 1910s (figure 3.13) (Santos et al 2021). Standards are an important prerequisite for the safe and sustainable reuse of unconventional water sources and other recovered products -they provide a basis for accountability and in turn can help build social and cultural acceptability (Salgot and Folch 2018;Taron, Drechsel and Gebrezgabher 2021;Bauer and Wagner 2022). The establishment standards for water quality form an important mechanism for ensuring human and environmental safety and can provide reassurance to increase trust (Salgot and Folch 2018).…”
Section: Examples Of Quality Standardsmentioning
confidence: 99%
“…However, in practice, farmers' awareness of risks is often low, protective gear is considered impractical for the task and climate, and any observed health problems, such as skin irritations, are accepted as a professional challenge well balanced by the economic benefit [39]. A review of cases from Africa and Asia showed that risks, risk awareness, and risk reduction can have distinct gender dimensions from farm to fork which have to be considered to make risk reduction successful [57].…”
Section: Targeting Kitchens Not (Only) Farms Within the Multi-barrier...mentioning
confidence: 99%